Interactive Augmented Reality Digital Comics to Enhance Understanding of Thayyibah Sentences in Elementary Schools - Ani Nur Aeni; Liyra Aulia Azzahra; Indira Aliya Rosmaida; Nurie Yanti Permatasari (Universitas Pendidikan Ganesha, 2025)
One of the major challenges in the learning process, including in Islamic Religious Education (IRE), is the decline in students’ ethical and moral behavior accompanied by low learning motivation. This condition is further exacerbated by the limited integration of educational technology, resulting in monotonous learning experiences that are less relevant to the characteristics of today’s digital generation. This study aims to analyze and develop an interactive digital comic media based on Augmented Reality (AR) to enhance elementary school students’ understanding and application of thayyibah expressions. The study employed a Design and Development (D&D) research method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects involved elementary school students and an Islamic Religious Education teacher. Data were collected through observations, questionnaires, and documentation, using expert validation sheets and user response questionnaires as research instruments. Data analysis was conducted using quantitative methods to determine the validity level of the developed media and qualitative analysis to examine feedback from students and teachers. The results indicate that the AR-based digital comic media demonstrates a very high level of feasibility in both content and media aspects and effectively increases students’ interest and engagement in learning. This study concludes that the use of AR-based digital comic media represents an innovative solution for Islamic Religious Education learning, not only in improving students’ cognitive outcomes but also in fostering moral values and strengthening learning motivation at the elementary school level.